2022
DOI: 10.1007/s10639-022-11177-3
|View full text |Cite
|
Sign up to set email alerts
|

Interacting with educational chatbots: A systematic review

Abstract: Chatbots hold the promise of revolutionizing education by engaging learners, personalizing learning activities, supporting educators, and developing deep insight into learners’ behavior. However, there is a lack of studies that analyze the recent evidence-based chatbot-learner interaction design techniques applied in education. This study presents a systematic review of 36 papers to understand, compare, and reflect on recent attempts to utilize chatbots in education using seven dimensions: educational field, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(180 citation statements)
references
References 96 publications
1
70
0
2
Order By: Relevance
“…The literature on chatbots in education and games for learning is limited. There are few studies on gamification and conversational AI in education [ 46 ]. For example, Lin et al [ 36 ] related a platform for collecting, evaluating, and annotating human–chatbot interactions.…”
Section: Related Workmentioning
confidence: 99%
“…The literature on chatbots in education and games for learning is limited. There are few studies on gamification and conversational AI in education [ 46 ]. For example, Lin et al [ 36 ] related a platform for collecting, evaluating, and annotating human–chatbot interactions.…”
Section: Related Workmentioning
confidence: 99%
“…The application of QA systems through the use of chatbots has been well documented in the educational sphere (Kuhail et al, 2022 ), with many specific features identified as being crucial to how students learn. An important function that educational chatbots should possess is the ability to scaffold the learning of an individual (Kim et al, 2022a ) by teaching them a certain topic or concept step-by-step, slowly building competency until a student is able to reach an acceptable level of mastery (Gazulla et al, 2022 ).…”
Section: Review Of Existing Literaturementioning
confidence: 99%
“…This chatbot would be able to provide a customisable visualisation of the students’ engagement statistics on the platform, allowing students to better organize their study sessions. Finally, another useful function that chatbots possess for education is the ability to read human affect, and potentially modify emotional states through empathetic responses (Kuhail et al, 2022 ). Words of encouragement, affirmation, or even motivational quotes, benefit students’ learning process due to the integral link between emotions and educational cognition (Hasan et al, 2020 ).…”
Section: Review Of Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…O uso de sistemas de conversac ¸ão tem se tornado cada vez mais popular devido ao seu potencial em simular diálogos humanos, possibilitando assim automatizar tarefas e reduzir custos [Kuhail et al 2022]. Existem diversos exemplos de aplicac ¸ões de chatbots em vários domínios, incluindo saúde [Chang et al 2022], servic ¸os ao consumidor [Misischia et al 2022], educac ¸ão [Oliveira et al 2010, Mondal et al 2018], entre outros.…”
Section: Introduc ¸ãOunclassified